Penerapan Aplikasi Simulasi Liveware 2.3 pada Mata Kuliah Dasar Teknik Tenaga Listrik - I Gede Budi Mahendra; Jocke Jonathan Rapar (Departement of Mathematics Education, 2023)
This study aims to determine the effect of using the Liveware 2.3 simulation application on student learning outcomes in the Basic Electrical Engineering Course in the Department of Electrical Engineering Education, Manado State University. This research is a pre-experimental study with a one-group pretest-posttest design. The population of this study were students in semester 1 class of 2022 majoring in Electrical Engineering Education. The sample taken consisted of one class, namely Class A1 2022, which consisted of 18 people. The data analysis technique used to analyze the research data is by testing through statistical calculations. Student learning outcomes after being given treatment show better results, this can be seen in the average pre-test score of 51.23 and post-test of 72.50. The increase difference is 21.27. The results of the t-test show an increase in learning outcomes with a Tcount of 2.23 which is consulted on Ttable 1.64. Thus, student learning outcomes after being treated with the Liveware 2.3 simulation application show good results. Student learning outcomes after being given treatment (post-test) are better than before being given treatment (pre-test). With an average learning result of 72.50 and obtained Tcount = 2.23>Ttable = 1.64.